Preparation, characterization and photocatalytic performance of heterostructured CuO–ZnO-loaded composite nanofiber membranes - Fang, Wei; Yu, Liang; Xu, Lan (Beilstein Journal of Nanotechnology, 2020)
Inorganic semiconductor oxides loaded on composite nanofibers (CNFs) have been widely applied in environmental monitoring, industry, aviation, and transportation. In this paper, heterostructured CuO–ZnO-loaded CNF membranes (CNFMs) were prepared successfully by a combination of electrospinning, heat treatment, and hydrothermal synthesis. The influence of the synthesis parameters on morphology, structure, and properties of the CNFMs was investigated, and the optimal process parameters were determined. Then, the CNFMs obtained with optimal process parameters were applied for the photocatalytic degradation of methyl orange. It was found that the CNFMs could be reused to degrade methyl orange at least three times, and the degradation rate remained above 90%.
Keywords: electrospinning; composite nanofibers; heterostructured CuO–ZnO; hydrothermal synthesis; photocatalysis; semiconductor oxide